2021
DOI: 10.1111/ejn.15404
|View full text |Cite
|
Sign up to set email alerts
|

Time course effect of corticospinal excitability for motor imagery

Abstract: This study examined the effect of temporal changes in corticospinal excitability in motor imagery (MI) and the effect of real‐time guides for MI on excitability changes. The MI task involved wrist flexion and motor evoked potentials using transcranial magnetic stimulation were recorded and examined from the flexor carpi radialis. Ballistic (momentary MI) and tonic (continuous MI) conditions were used, and the duration of each MI was different. In Experiment 1, each MI task was performed using an acoustic trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The goal of standardization and automation of sports has been achieved through the development of professional sports models. However, research has shown that current higher education and physical education in higher education institutions have had a significant impact on the dual thinking of "competence," while practical training, technical training, and physical training are faced with a "dual" confrontation (Takenaka et al, 2023). The focus is on individual sports and professional training.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The goal of standardization and automation of sports has been achieved through the development of professional sports models. However, research has shown that current higher education and physical education in higher education institutions have had a significant impact on the dual thinking of "competence," while practical training, technical training, and physical training are faced with a "dual" confrontation (Takenaka et al, 2023). The focus is on individual sports and professional training.…”
Section: Background Of the Studymentioning
confidence: 99%
“…We have previously reported that a real‐time guide for MI with visual priming for timing and intensity could improve the MI accuracy for detecting changes in the corticospinal excitability (Takenaka et al, 2021). Here, we further integrate previous research showing that MI was more effective at enhancing corticospinal excitability when participants additionally observed the movement of others (Mouthon et al, 2015; Sun et al, 2016; Tsukazaki et al, 2012; Wright et al, 2014, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we further integrate previous research showing that MI was more effective at enhancing corticospinal excitability when participants additionally observed the movement of others (Mouthon et al, 2015; Sun et al, 2016; Tsukazaki et al, 2012; Wright et al, 2014, 2015, 2016). This combination approach is potentially more effective in improving motor performance (Eaves et al, 2016); a real‐time MI guide has exhibited similar effects (Takenaka et al, 2021). In the present study, MI was used with a visual real‐time guide to improve and enhance its accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Pfurtscheller and Neuper, 1997) also have shown that stroke patients can perform motor imagery to partially activate the damaged motor network (Fumanal-Idocin et al, 2021). In addition, studies have found that the rehabilitation treatment model combining BCI and VR technology is suitable for people suffering from stroke (Varsehi and Firoozabadi, 2021), depression, addiction and other diseases (Takenaka et al, 2021). VR-guided action offers the advantages of intuitive and specific actions and a strong sense of substitution (Velasquez-Martinez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%